Pemanfaatan Bahan Alam Untuk Pencegahan Anemia pada Remaja Putri di SMK Muhammadiyah 1 Samarinda - Asty Delima Ary; Maharani Endar Dwipari; Vanessa Paradis Ilyas; Ghina Nur Azizah; Jaka Fadraersada (Universitas Respati Indonesia, 2026)
Anemia is a condition characterized by a decrease in the body’s hemoglobin levels. The management of anemia does not only depend on medical therapy, as it can also utilize Indonesia’s abundant biodiversity as a natural alternative, since many plants contain iron and other nutrients that support hemoglobin formation. This activity aimed to increase the knowledge of 10th and 11th grade female students at SMK 1 Muhammadiyah Samarinda regarding the potential use of natural ingredients to prevent and manage anemia. The health promotion activity was conducted using a lecture method supported by leaflet media. The activity began with a pre-test administered through Google Form, followed by the presentation of educational material, a question-and-answer session, and a post-test. A total of 19 participants took part in this activity. The results of the health promotion activity showed that the average pre-test score was 81.58%, while the average post-test score increased to 94.21%. The conclusion that can be the health promotion activity successfully improved the knowledge of 10th and 11th grade female students at SMK 1 Muhammadiyah Samarinda regarding the potential use of natural ingredients for the prevention and management of anemia.